JOQARÍ OQÍW ORÍNLARÍNDA BILIM SAPASÍN ASÍRÍW MÁSELELERI - Sabirova, M.; Yerejepov М. (SCIENCE and SOCIETY, 2024)
The article presents factors that influence the improvement of the quality of education in higher educational institutions; the organization of education is also considered as a complex system that includes the process of providing and managing education.